Implementasi Komunikasi Green Ship Strategy 2020-2025 Di Pelabuhan Kendari Sulawesi Tenggara Untuk Meningkatkan Investasi Daerah - Khairatun Niswa Aceh 26; Henni Gusfa; Muhd Ar.Imam Riauan; Yuliawati Yuliawati; Suratani Bangko; Mikke Setiawati; Ramdanis Ramdanis (Journal of Innovative and Creativity, 2026)
Maritime transportation and communicating the concept of a green environment in the sea is an interesting phenomenon in social science, irregular transportation services and the situation of manual transportation infrastructure both land and sea transportation which has become a culture are now interesting things to study. With port management based on the environment and public safety, it will provide an increase in regional investment. Changes that are oriented towards regional investment, especially the eastern region, are urgent in supporting national development programs starting at the policy level carried out at every port in Indonesia to evaluation. Therefore, the purpose of this study is to provide a model of the implementation of the green ship strategy policy communication 2020-2025 at the Kendari port, Southeast Sulawesi. The method used is a case study at the port in the city of Kendari as a port performance that carries out its functions in business, social and eastern community activities. The theory used is the theory of organizational communication from Karl Weick, messages as a negotiation strategy from O'keefe, Pentheliks model. Concept of policy implementation from George Edward III, the informant of this research is the management level of the operational division and the technical division at the Kendari port and the service related to greenship policy. The result of this study is that the greenship strategy policy is communicated with the control power of the central Makassar Pelindo company based on the rules or instructions in the technical and operational division of the Kendari branch of Pelindo. The role of the operational division and technical division as actors is to conduct CO2 emission tests, manage port waste and manage green open fields. After carrying out these activities, submit a report to the head office and submit a report to the city environmental service. The role played by Pelindo in this implementation has been carried out in accordance with the main tasks and functions. Communication modeling in the implementation of the greenship strategy policy includes negotiation and persuasion strategies, Pelindo company digital communication, penthelik-based collaborative communication. Communication controlled by the power of the bureaucracy is published as a form of responsibility on the company's website. This implementation is still carried out independently and has not been coordinated with cross-agency in the integration of environmental programs, meaning that pentahelic synergies have not been implemented. Therefore, the recommendation for this research is that Pelindo Kendari requires a communication structure that involves policy debate, crisis communication and issue management. The available resources in the implementation are limited with the use of waste for green open spaces so that the common awareness to lead the transportation sector that inspires investment growth has not materialized. communication management that makes external relations with Pelindo companies can lead to the development of regional investment in Pelindo, which is already more mature in its preparations in logistics and infrastructure for the tourism and fisheries industry.